Melatonin and Kidney Health: From Fetal Stage to Later Life - Tang, Kuo-Shu; Ho, Chun-Yi; Hsu, Chien-Ning; Tain, You-Lin (International journal of molecular sciences, 2023)
Melatonin, an endogenous hormone mainly released at night by the pineal gland, has multifaceted biofunctions. Emerging evidence points to melatonin having a crucial role in kidney health and disease. As the prevalence of chronic kidney disease (CKD) is still rising, a superior strategy to advance global kidney health is needed to not just treat CKD, but prevent it early on. Adult kidney disease can have its origins in early life. This review aims to evaluate the recent literature regarding melatonin’s effect on kidney development, its clinical uses in the early stage of life, animal models documenting preventive applications of melatonin on offspring’s kidney-related disease, and a thorough summary of therapeutic considerations concerning melatonin supplementation.